Maximum number of minimum dominating and minimum total dominating sets - Godbole, Anant; Jamieson, Jessie D.; Jamieson, William (Utilitas Mathematica, 2014)
Given a connected graph with domination (or total domination) number γ ≥ 2, we ask for the maximum number mγ and m T,γof dominating and total dominating sets of size γ. An exact answer is provided for γ = 2 and lower bounds are given for m γ and mT,γ;γ≥3.